A new score for life-threatening ventricular arrhythmias and sudden cardiac death in adults with transposition of the great arteries and a systemic right ventricle. (8th June 2022) - Ladouceur, Magalie; Van De Bruaene, Alexander; Kauling, Robert; Budts, Werner; Roos-Hesselink, Jolien; Albert, Sandra Villagrá; Perez, Inmaculada Sanchez; Sarubbi, Berardo; Fusco, Flavia; Gallego, Pastora; Rodriguez-Puras, Maria Jose; Bouchardy, Judith; et al.
Abstract: Aims: To investigate the incidence of major adverse ventricular arrhythmias and related events (MAREs) and to develop a stratification tool predicting MAREs in adults with a systemic right ventricle (sRV). Methods and results: In a multicentre approach, all adults (≥16 years old) with a sRV undergoing follow-up between 2000 and 2018 were identified. The incidence of MAREs, defined as sudden cardiac death, sustained ventricular tachycardia, and appropriate implantable cardioverter-defibrillator (ICD) therapy, was analysed. The association of MAREs with clinical, electrical, and echocardiographic parameters was evaluated. A total of 1184 patients (median age 27.1 years; interquartile range 19.9–34.9 years; 59% male; 70% with atrial switch repair for D-transposition of the great arteries) were included. The incidence of MAREs was 6.3 per 1000 patient-years. On multivariate analysis, age, history of heart failure, syncope, QRS duration, severe sRV dysfunction and at least moderate left ventricular outflow tract obstruction were retained in the final model with a C-index of 0.78 [95% confidence interval (CI) 0.72–0.83] and a calibration slope of 0.93 (95% CI 0.64–1.21). For every five ICDs implanted in patients with a 5-year MARE risk >10%, one patient may potentially be spared from a MARE. Conclusion: Sudden cardiac death remains a devastating cause of death in a contemporary adult cohort with a sRV. A prediction model based on clinical, electrocardiographic, and echocardiographic parameters was devised to estimate MARE risk and to identify high-risk patients who may benefit from primary prevention ICD implantation. Structured Graphical Abstract: Structured Graphical Abstract Prediction of malignant ventricular arrhythmia and/or sudden cardiac death in the systemic right ventricle (sRV). Major adverse ventricular arrhythmias and related event (MARE) risk prediction model and Kaplan–Meier survival curves for freedom from MAREs plotted and compared according to the risk groups. Shaded areas correspond to 95% confidence intervals. LVOTO, left ventricular outflow tract obstruction; MAREs, major adverse ventricular arrhythmias and related events.